2016
DOI: 10.1007/s10549-016-3854-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of curcumin-treated human breast stem cells identifies a role for stearoyl-coa desaturase in breast cancer prevention

Abstract: Curcumin is a potential agent for both the prevention and treatment of cancers. Curcumin treatment alone, or in combination with piperine, limits breast stem cell self-renewal while remaining non-toxic to normal differentiated cells. We paired fluorescence activated cell sorting with RNA sequencing to characterize the genome-wide changes induced specifically in normal breast stem cells following treatment with these compounds. We generated genome-wide maps of the transcriptional changes that occur in epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…Despite the lack of overlap between these populations, these cell maintain a cellular plasticity allowing them to inter-convert in a process regulated by the tumor microenvironment (Liu et al, 2013). Similarly, we previously showed that ALDH + or CD44 + normal mammary cells cultured as mammospheres also have distinct epithelial or mesenchymal phenotypes relative to each other (Colacino et al, 2016). In the current study, we expanded upon these observations by using CD24 + cells as a differentiated cell anchor to compare the gene expression signatures of ALDH + and CD44 + cells.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Despite the lack of overlap between these populations, these cell maintain a cellular plasticity allowing them to inter-convert in a process regulated by the tumor microenvironment (Liu et al, 2013). Similarly, we previously showed that ALDH + or CD44 + normal mammary cells cultured as mammospheres also have distinct epithelial or mesenchymal phenotypes relative to each other (Colacino et al, 2016). In the current study, we expanded upon these observations by using CD24 + cells as a differentiated cell anchor to compare the gene expression signatures of ALDH + and CD44 + cells.…”
Section: Discussionmentioning
confidence: 91%
“…Normal mammary cells were stained for CD44, and CD24 expression and ALDH activity accessed by the Aldefluor assay as described previously (Colacino et al, 2016) and analyzed or sorted on a Beckman Coulter MoFlo Astrios at the University of Michigan Flow Cytomtery core facility. Briefly, single mammary cells were first incubated with a lineage depletion cocktail that consisted of biotinylated antibodies targeted against CD45, HLA-DR, CD14, CD31, CD41, CD19, CD235a, CD56, CD3, CD16, and CD140b (all from eBioscience, except for CD140b (Biolegend) and CD41 (Acris)).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Non-pathogenic breast tissue was isolated from women undergoing voluntary reduction mammoplasty at the University of Michigan. Breast tissue was mechanically and enzymatically digested as previously described (Colacino et al 2016;Dontu et al 2003) to yield a viable single cell suspension of human mammary cells. This study was reviewed and approved by the University of Michigan Institutional Review Board (HUM00042409).…”
Section: Human Tissue Procurementmentioning
confidence: 99%
“…The primary mammosphere formation assay is a surrogate readout of breast stem cell activity, while the secondary mammosphere formation assay is a readout of breast stem cell self-renewal capacity (Dontu et al 2003). Single primary human breast cells were plated in mammosphere formation conditions, in the presence of 0.25µM or 2.5µM cadmium chloride or vehicle control following our previously established protocol (Colacino et al 2016). Briefly, cells were plated at a concentration of 100,000/mL in ultralow attachment plates (Corning) conditions in MammoCult (StemCell) media.…”
Section: Cadmium Dosing and Mammosphere Formationmentioning
confidence: 99%